Multiple modulatory roles of serotonin in chronic pain and injury-related anxiety - Hao, Shun; Shi, Wantong; Liu, Weiqi; Chen, Qi-Yu; Zhuo, Min (Frontiers in Synaptic Neuroscience, 2023)
Chronic pain is long-lasting pain that often persists during chronic diseases or after recovery from disease or injury. It often causes serious side effects, such as insomnia, anxiety, or depression which negatively impacts the patient’s overall quality of life. Serotonin (5-HT) in the central nervous system (CNS) has been recognized as an important neurotransmitter and neuromodulator which regulates various physiological functions, such as pain sensation, cognition, and emotions ‒ especially anxiety and depression. Its widespread and diverse receptors underlie the functional complexity of 5-HT in the CNS. Recent studies found that both chronic pain and anxiety are associated with synaptic plasticity in the anterior cingulate cortex (ACC), the insular cortex (IC), and the spinal cord. 5-HT exerts multiple modulations of synaptic transmission and plasticity in the ACC and the spinal cord, including activation, inhibition, and biphasic actions. In this review, we will discuss the multiple actions of the 5-HT system in both chronic pain and injury-related anxiety, and the synaptic mechanisms behind them. It is likely that the specific 5-HT receptors would be new promising therapeutic targets for the effective treatment of chronic pain and injury-related anxiety in the future.